Online-Exclusive or Hybrid? Channel Merchandising Strategies for Ship-to-Store Implementation - Ertekin, Necati; Gümüş, Mehmet; Nikoofal, Mohammad E. (Management Science, 2022)
We study how merchandising products as online-exclusive (i.e., products available only online) versus hybrid (i.e., products available both online and offline) can improve the performance of ship-to-store (STS) services, an omnichannel retail fulfillment initiative that allows customers to pick up their online orders in-store. First, using a stylized model, we theoretically demonstrate that although STS is likely to increase sales, it may also entail the risk of losing some customers by exposing them to alternative products at nearby competitors during in-store pickup visits. Online-exclusive products and hybrid products are subject to this tradeoff at different degrees. To minimize the risk of STS, we theoretically propose a channel merchandising strategy for the STS implementation. Next, we empirically test our theoretical predictions using data from an omnichannel retailer that launched the STS functionality. We also conduct an empirical counterfactual analysis to quantify the benefits of our proposed channel merchandising strategy. Overall, our theoretical model coupled with the empirical analysis suggests that to improve the performance of STS implementation, an omnichannel retailer should offer (i) products that are somewhat generic, low-priced, and with high in-store availability as online-exclusive and (ii) products that are somewhat unique, high-priced, and with low in-store availability as hybrid. The counterfactual analysis reveals that the proposed channel merchandising strategy can improve STS performance by increasing overall retail sales by another 2.7% for the focal retailer. This paper was accepted by Vishal Gaur, operations management.